Evaluating companies for mergers and acquisitions - Hassan, Ibne; Ghauri, Pervez N. (International business and management, ISSN 1876-066X, 2014)
This volume in the IBM series investigates how the evaluation of a target firm influence the outcome of mergers and acquisitions (M&As). Co-authored by international business expert Pervez Ghauri, it highlights the processes that evaluate potential acquisition targets, and how a proper evaluation can positively influence the M&A performance.
Keywords: Business & Economics : International : General; International business; Consolidation and merger of corporations